The ability to perform a post-traumatic examination as an indicator of the effects of teaching emergency medicine at the successive stages of the educational process: medical students, trainee physicians. - Pakulski, Cezary; Denisiuk, Maciej (Journal of Medical Science, 2018)
Introduction. Emergency management at the accident site is often of key importance for the later fate of patients who have sustained severe injuries. The scheme for post-traumatic examination has been developed to improve dealing with trauma patients. Aim. The aim of this study was to analyze the effects of teaching emergency medicine to students and graduates of the Faculty of Medicine in Szczecin, on the basis of their ability to carry out post-traumatic examination. The skills at recognizing a direct threat to life and performing basic life-saving procedures were appraised. Material and Methods. The study involved 81 individuals, who were evaluated three times at different stages of their educational process. Groups I and II comprised of fifth year students before and after an emergency medicine course, and group III consisted of trainee physicians. The Laerdal MegaCode Kelly manikin was employed in the project. Each of the simulated patients had the same external injury symptoms and parameters of vital functions. Results. Evaluation of vital functions was correctly done by 14.8% of group I, 59.3% of group II, and no one in group III. A quick post-traumatic examination was performed properly by 11.2% of group I, 55.5% of group II, and no one in group III. Conclusions. Group I lacked the ability to perform post-traumatic examination and first aid procedures. Participation in emergency medicine courses had positive effects on the participants’ skills (group II). The ability of trainee physicians (group III) to perform the majority of the tested elements of post-traumatic examination, including first aid procedures, noticeably declined and reached the initial level.